Evaluation of the COVID-19 vaccine effectiveness on the outcomes of COVID 19 disease in Iran: a test-negative case-control study - Khosravi Shadmani, Fatemeh; Moradi, Ghobad; Naghipour, Mohammadreza; Torkaman Asadi, Fatemeh; Ahmadi, Ali; Mirahmadizadeh, Alireza; Haghdoost, Ali Akbar; Mesgarpour, Bita; Zahraei, Seyed Mohsen; Goya, Mohammad Mehdi; Mokhtari, Majid; Safari-Faramani, Roya; et al. (Frontiers in Immunology, 2024)
Introduction: This study measures the COVID-19 vaccine effectiveness (CVE) against hospital admission and severe COVID-19. Methods: This study is a test-negative case-control design using data from eight provinces in April, 2021 until March, 2022. The individuals were classified as cases and controls based on the results of the RT-PCR test for SARS-CoV-2 and matched based on the timing of the test being conducted as well as the timing of hospital admission. The measure of association was an odds ratio (OR) by univariate and multiple logistic regression. The multiple logistic regression has been carried out to take confounding factors and potential effect modifiers into account. The CVE was computed as CVE = (1 -OR)*100 with 95% confidence interval.Results: Among 19314 admitted patients, of whom 13216 (68.4%) were cases and 6098 (31.6%) were controls, 1313 (6.8%) died. From total, 5959 (30.8%) patients had received the vaccine in which one, two, and booster doses were 2443 (12.6%), 2796 (14.5 ٪ ), and 720 (3.7٪), respectively.The estimated adjusted effectiveness of only one dose, two doses and booter vaccination were 22% (95% CI: 14%-29%), 35% (95% CI: 29%-41%) and 33% (95% CI: 16%-47%), respectively.In addition, the adjusted vaccine effectiveness against severe outcome was 33% (95% CI: 19%-44%), 34% (95% CI: 20%-45%) and 20% (95% CI: -29%-50%) for those who received one, two and booster vaccinations, respectively.Our study concluded that full vaccination, though less effective compared to similar studies elsewhere, decreased hospital admissions and deaths from COVID-19 in Iran, particularly during the Delta variant period, with an observed decline during the Omicron variant dominance.